Counter electrode for photoelectric conversion element, dye-sensitized solar cell, solar cell module, and method for manufacturing a counter electrode for photoelectric conversion element

JP2026166597APending Publication Date: 2026-10-14ZEON CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059632
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0018】 本発明によれば、色素増感型太陽電池等の光電変換素子の電流密度および変換効率を向上し得る光電変換素子用対向電極を提供することができる。 また、本発明によれば、電流密度および変換効率に優れる色素増感型太陽電池と、この色素増感型太陽電池を用いた太陽電池モジュールを提供することができる。 そして、本発明によれば、色素増感型太陽電池等の光電変換素子の電流密度および変換効率を向上し得る光電変換素子用対向電極の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166597000002
    Figure 2026166597000002
  • Figure 2026166597000003
    Figure 2026166597000003
  • Figure 2026166597000001
    Figure 2026166597000001
Patent Text Reader

Abstract

To provide a counter electrode for a photoelectric conversion element that can improve the current density and conversion efficiency of the photoelectric conversion element, such as a dye-sensitized solar cell. [Solution] A counter electrode for a photoelectric conversion element having a support and a catalyst layer formed on the support. The catalyst layer comprises a porous carbon material containing two or more transition metals, carbon nanotubes, and conductive carbon material other than the porous carbon material containing the two or more transition metals and the carbon nanotubes. The porous carbon material containing the two or more transition metals is a zeolite imidazolate framework carbide, and the micropore capacity of the zeolite imidazolate framework carbide is 0.09 mL / g or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a counter electrode for a photoelectric conversion element, a dye-sensitized solar cell, a solar cell module, and a method for manufacturing a counter electrode for a photoelectric conversion element. [Background technology]

[0002] In recent years, solar cells have attracted attention as photoelectric conversion elements that convert light energy into electricity. Among them, dye-sensitized solar cells are attracting attention because they can generate electricity stably over a wide irradiation range and can be manufactured using relatively inexpensive materials without requiring large-scale equipment.

[0003] For example, Patent Document 1 proposes a catalytic electrode that can be manufactured using inexpensive materials and a simple manufacturing method, and that can rapidly reduce the oxidized form of an oxidation-reduction pair contained in an electrolyte, as well as a dye-sensitized solar cell equipped with the same. Here, the catalytic electrode of Patent Document 1 is provided in a dye-sensitized solar cell having at least a light-transmitting semiconductor electrode containing a dye that has a photosensitizing effect, and an electrolyte layer containing at least chemical species that form an oxidation-reduction pair, and is positioned opposite the semiconductor electrode via the electrolyte layer. One embodiment of the catalytic electrode is described, which comprises at least an electrode substrate, a conductive polymer, and an organometallic complex, wherein the organometallic complex is dispersed and supported in the conductive polymer. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2006-202562 [Overview of the project] [Problems that the invention aims to solve]

[0005] However, conventional dye-sensitized solar cells still had room for further improvement in short-circuit current density (hereinafter sometimes simply referred to as "current density") and energy conversion efficiency (hereinafter sometimes simply referred to as "conversion efficiency").

[0006] Therefore, the present invention aims to provide a counter electrode for a photoelectric conversion element that can improve the current density and conversion efficiency of the photoelectric conversion element, such as a dye-sensitized solar cell. Furthermore, the present invention aims to provide a dye-sensitized solar cell that is excellent in current density and conversion efficiency, and a solar cell module using this dye-sensitized solar cell. Furthermore, the present invention aims to provide a method for manufacturing a counter electrode for a photoelectric conversion element that can improve the current density and conversion efficiency of the photoelectric conversion element, such as a dye-sensitized solar cell. [Means for solving the problem]

[0007] The inventors diligently conducted research with the aim of solving the above problems. As a result, the inventors discovered that by using a counter electrode for a photoelectric conversion element having a support and a catalyst layer formed on the support, wherein the catalyst layer comprises a porous carbon material containing two or more transition metals, carbon nanotubes, the porous carbon material containing the two or more transition metals and a conductive carbon material other than the carbon nanotubes, and the porous carbon material containing the two or more transition metals is a zeolite imidazolate framework carbide having a micropore capacity of a predetermined value or more, it is possible to form a photoelectric conversion element such as a dye-sensitized solar cell that is excellent in current density and conversion efficiency, and thus completed the present invention.

[0008] In other words, the present invention aims to advantageously solve the above problems, and according to the present invention, the following counter electrodes for photoelectric conversion elements [1] to [3], the following dye-sensitized solar cell [4], the following solar cell module [5], and the following methods for manufacturing counter electrodes for photoelectric conversion elements [6] to [9] are provided.

[0009] [1] A counter electrode for a photoelectric element, comprising a support and a catalyst layer formed on the support, wherein the catalyst layer comprises a porous carbon material containing two or more transition metals, carbon nanotubes, and conductive carbon material other than the porous carbon material containing the two or more transition metals and the carbon nanotubes, the porous carbon material containing the two or more transition metals being a zeolite imidazolate framework carbide, and the micropore capacity of the zeolite imidazolate framework carbide being 0.09 mL / g or more. In this invention, "micropores" refers to pores with a diameter of 2 nm or less, "mesopores" refers to pores with a diameter greater than 2 nm and less than 50 nm, and "total pores" refers to both micropores and mesopores. In this invention, the "micropore capacity," "mesopore capacity," and "total pore capacity" of the zeolite imidazolate framework carbide can be measured using the methods described in the examples of this specification.

[0010] [2] The counter electrode for a photoelectric conversion element according to [1] above, wherein the average particle size of the zeolite imidazolate framework carbide is 0.1 μm or more and 2.0 μm or less. In this invention, the "average particle size" of the zeolite imidazolate framework carbide can be measured using the method described in the examples of this specification.

[0011] [3] The counter electrode for a photoelectric conversion element according to [1] or [2] above, wherein the two or more transition metals include at least one of zinc and cobalt.

[0012] [4] A dye-sensitized solar cell having a photoelectrode, an electrolyte layer, and a counter electrode in this order, wherein the counter electrode is a counter electrode for a photoelectric conversion element as described in any of [1] to [3] above.

[0013] [5] A solar cell module comprising the dye-sensitized solar cells described in [4] above, connected in series and / or in parallel.

[0014] 〔6〕A method for producing a counter electrode for a photoelectric conversion element, comprising the step of forming a catalyst layer on a support using a composition comprising a porous carbon material containing two or more transition metals, carbon nanotubes, and a conductive carbon material other than the porous carbon material containing two or more transition metals and the carbon nanotubes, wherein the porous carbon material containing two or more transition metals is a zeolite imidazolate framework carbide, and the micropore volume of the zeolite imidazolate framework carbide is 0.09 mL / g or more.

[0015] 〔7〕The method for producing a counter electrode for a photoelectric conversion element according to the above〔6〕, wherein the average particle diameter of the zeolite imidazolate framework carbide is 0.1 μm or more and 2.0 μm or less.

[0016] 〔8〕The method for producing a counter electrode for a photoelectric conversion element according to the above〔6〕or〔7〕, further comprising the step of heating a zeolite imidazolate framework containing two or more transition metals at a temperature of 750°C or more and 900°C or less in a reducing atmosphere to obtain the zeolite imidazolate framework carbide, before the step of forming the catalyst layer. In the present invention, the "reducing atmosphere" means an atmosphere composed of a mixed gas of hydrogen and an inert gas (such as nitrogen or a rare gas).

[0017] 〔9〕The method for producing a counter electrode for a photoelectric conversion element according to the above〔8〕, wherein the organic ligand contained in the zeolite imidazolate framework is 2-methylimidazole. [[ID=16】Effects of the Invention]

[0018] According to the present invention, it is possible to provide a counter electrode for a photoelectric conversion element that can improve the current density and conversion efficiency of a photoelectric conversion element such as a dye-sensitized solar cell. Further, according to the present invention, it is possible to provide a dye-sensitized solar cell excellent in current density and conversion efficiency, and a solar cell module using this dye-sensitized solar cell. Further, according to the present invention, it is possible to provide a method for producing a counter electrode for a photoelectric conversion element, which can improve the current density and conversion efficiency of a photoelectric conversion element such as a dye-sensitized solar cell. Brief Description of the Drawings

[0019] [Figure 1] It is a diagram showing a schematic configuration of an example of a dye-sensitized solar cell. [Figure 2] It is a diagram showing an observation image of a zeolite imidazolate framework carbide obtained by a field emission scanning electron microscope. Modes for Carrying Out the Invention

[0020] The counter electrode for a photoelectric conversion element of the present invention can be used as a counter electrode for photoelectric conversion elements such as dye-sensitized solar cells, organic thin-film solar cells, or perovskite solar cells. Among these, it is suitably used as a counter electrode for a dye-sensitized solar cell. The counter electrode for a photoelectric conversion element of the present invention can be produced by the method for producing a counter electrode for a photoelectric conversion element of the present invention. Further, the dye-sensitized solar cell of the present invention is a dye-sensitized solar cell having a photoelectrode, an electrolyte layer, and a counter electrode in this order, and has the counter electrode for a photoelectric conversion element of the present invention as the counter electrode. Furthermore, the solar cell module of the present invention is formed by connecting the dye-sensitized solar cells of the present invention in series and / or in parallel.

[0021] (Counter Electrode for Photoelectric Conversion Element) The counter electrode for a photoelectric conversion element of the present invention (hereinafter also simply referred to as "counter electrode") has a support and a catalyst layer formed on the support. Furthermore, the counter electrode of the present invention comprises a catalyst layer comprising a porous carbon material containing two or more transition metals, carbon nanotubes, and conductive carbon materials other than the porous carbon material containing the two or more transition metals and the carbon nanotubes, wherein the porous carbon material containing the two or more transition metals is a zeolite imidazolate framework carbide, and the micropore capacity of the zeolite imidazolate framework carbide is 0.09 mL / g or more. By using the counter electrode of the present invention having the above features, the current density and conversion efficiency of photoelectric conversion elements such as dye-sensitized solar cells can be improved.

[0022] <Support> The support plays the role of supporting the catalyst layer. In this invention, since the carbon nanotubes and conductive carbon material contained in the catalyst layer are conductive, a conductive layer is not necessarily required between the support and the catalyst layer. However, from the viewpoint of ensuring better current flow, it is preferable that a conductive layer be formed on at least the surface portion of the support that can come into contact with the catalyst layer. As the support for the counter electrode, known materials can be used. Specifically, as the support for the counter electrode, a support made of transparent resin or a support made of glass can be used. Among these, it is preferable to use a support made of transparent resin because it is possible to efficiently form dye-sensitized solar cells that have excellent conversion efficiency. Examples of transparent resins include synthetic resins such as cycloolefin polymer (COP), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), syndiotactic polystyrene (SPS), polyphenylene sulfide (PPS), polycarbonate (PC), polyarylate (PAr), polysulfone (PSF), polyethersulfone (PES), polyetherimide (PEI), and transparent polyimide (PI).

[0023] The thickness of the support material can be determined appropriately depending on the application, but it is usually between 10 μm and 1000 μm. Furthermore, the light transmittance of the support (measurement wavelength: 500 nm) is preferably 60% or more, more preferably 75% or more, and even more preferably 80% or more.

[0024] <Catalyst layer> The catalyst layer functions as a catalyst in dye-sensitized solar cells when electrons are transferred from the counter electrode to the electrolyte layer. The catalyst layer according to the present invention is required to include a porous carbon material containing two or more transition metals, carbon nanotubes (hereinafter also referred to as "CNTs"), and conductive carbon materials other than the porous carbon material containing two or more transition metals and CNTs (hereinafter referred to as "other conductive carbon materials"). Furthermore, the catalyst layer according to the present invention may optionally further contain components other than those mentioned above (hereinafter referred to as "other components").

[0025] <<Porous carbon material>> Porous carbon materials consist of zeolite imidazolate framework carbides that are porous and contain two or more transition metals.

[0026] [Zeolite imidazolate framework carbide] Zeolite imidazolate framework carbides are produced by calcining a zeolite imidazolate framework containing two or more transition metals. Organic ligands contained in the zeolite imidazolate framework before calcination are thermally decomposed during calcination, and zeolite imidazolate framework carbides typically do not contain organic ligands.

[0027] Zeolite imidazolate framework carbides must contain two or more transition metals. If the zeolite imidazolate framework carbides contain one or fewer transition metals, the current density and conversion efficiency of the resulting photoelectric conversion element will decrease.

[0028] Here, the transition metals included in the zeolite imidazolate framework carbide are not particularly limited, but cobalt (Co), zinc (Zn), nickel (Ni), copper (Cu), manganese (Mn), chromium (Cr), and silver (Ag) are preferred. Furthermore, the zeolite imidazolate framework carbide preferably contains at least one of zinc and cobalt as transition metals, and more preferably contains both zinc and cobalt.

[0029] —Micropore Capacity— The micropore capacity of the zeolite imidazolate framework carbide must be 0.09 mL / g or higher. If the micropore capacity of the zeolite imidazolate framework carbide is less than 0.09 mL / g, the current density and conversion efficiency of the photoelectric conversion element will decrease. Furthermore, the micropore capacity of the zeolite imidazolate framework carbide is preferably 0.095 mL / g or more, more preferably 0.10 mL / g or more, preferably 0.20 mL / g or less, more preferably 0.16 mL / g or less, and even more preferably 0.12 mL / g or less. If the micropore capacity of the zeolite imidazolate framework carbide is 0.095 mL / g or more, it functions better as a porous carbon material, and the current density and conversion efficiency of the photoelectric conversion element can be further improved. On the other hand, if the micropore capacity of the zeolite imidazolate framework carbide is 0.20 mL / g or less, the curve factor of the photoelectric conversion element can be increased. The micropore capacity of the zeolite imidazolate framework carbide can be adjusted, for example, by changing the manufacturing conditions of the zeolite imidazolate framework carbide. For example, in the method for manufacturing a counter electrode for a photoelectric conversion element of the present invention, described later, the micropore capacity of the zeolite imidazolate framework carbide can be adjusted by changing the heating temperature in the carbide preparation step and whether or not a dispersion treatment step is performed. Alternatively, in the method for manufacturing a counter electrode for a photoelectric conversion element of the present invention, described later, the micropore capacity of the zeolite imidazolate framework carbide can be adjusted by changing the type of compound that forms the organic ligand or the transition metal-containing compound in the precursor preparation step.

[0030] —Total pore volume— In this invention, "total pores" refers to both micropores and mesopores, and "total pore volume" can be determined as the sum of micropore volume and mesopore volume.

[0031] -Average particle size- The average particle size of the zeolite imidazolate framework carbide is preferably 0.1 μm or more, more preferably 0.2 μm or more, even more preferably 0.3 μm or more, preferably 2.0 μm or less, more preferably 1.5 μm or less, even more preferably 1.0 μm or less, and particularly preferably 0.5 μm or less. If the average particle size of the zeolite imidazolate framework carbide is within the above range, the current density and conversion efficiency of the photoelectric conversion element can be further improved. The average particle size of the zeolite imidazolate framework carbide can be adjusted, for example, by changing the manufacturing conditions of the zeolite imidazolate framework carbide. For example, the average particle size of the zeolite imidazolate framework carbide can be adjusted by changing the heating temperature in the carbide preparation step in the manufacturing method for the counter electrode for the photoelectric conversion element of the present invention, which will be described later.

[0032] -BET specific surface area- The BET specific surface area of ​​the zeolite imidazolate framework carbide can be adjusted, for example, by changing the manufacturing conditions of the zeolite imidazolate framework carbide. For example, in the manufacturing method for the counter electrode for the photoelectric conversion element of the present invention, described later, the BET specific surface area of ​​the zeolite imidazolate framework carbide can be adjusted by changing the heating temperature in the carbide preparation step and whether or not a dispersion treatment step is performed.

[0033] <<Carbon nanotubes>> The CNTs included in the catalyst layer are not particularly limited, and single-walled CNTs and / or multi-walled CNTs can be used. However, the CNTs are preferably single-walled to five-walled, and more preferably single-walled CNTs. This is because using single-walled CNTs allows for further improvement of conductivity compared to using multi-walled CNTs.

[0034] Furthermore, it is preferable to use CNTs in which the ratio of the standard deviation of the diameter (σ) multiplied by 3 (3σ) to the average diameter (Av) (3σ / Av) is greater than 0.20 and less than 0.80, more preferably CNTs in which 3σ / Av is greater than 0.25, and even more preferably CNTs in which 3σ / Av is greater than 0.40. By using CNTs in which 3σ / Av is greater than 0.20 and less than 0.80, the conductivity can be sufficiently increased even with a small amount of CNTs added. Therefore, it is possible to suppress the increase in hardness of the catalyst layer (i.e., the decrease in flexibility) due to the addition of CNTs, and to obtain a catalyst layer that achieves both conductivity and flexibility at a sufficiently high level. The average diameter (Av) and standard deviation (σ: sample standard deviation) of CNTs can be determined by measuring the diameter (outer diameter) of 100 randomly selected CNTs using a transmission electron microscope. The average diameter (Av) and standard deviation (σ) of CNTs may be adjusted by changing the manufacturing method or conditions of the CNTs, or by combining multiple types of CNTs obtained by different manufacturing methods.

[0035] For carbon nanotubes (CNTs), the diameter measured as described above is plotted on the x-axis and its frequency on the y-axis. When this plotted and approximated by a Gaussian matrix, the resulting matrix typically follows a normal distribution.

[0036] Furthermore, the average diameter (Av) of the CNTs is preferably 2 nm or more, more preferably 2.5 nm or more, preferably 10 nm or less, and more preferably 6 nm or less. If the average diameter (Av) of the CNTs is 2 nm or more, the aggregation of CNTs can be suppressed and the dispersibility of CNTs can be improved. Also, if the average diameter (Av) of the CNTs is 10 nm or less, the conductivity and flexibility of the catalyst layer can be sufficiently improved.

[0037] Furthermore, it is preferable that the average length of the CNTs at the time of synthesis is 100 μm or more. However, the longer the CNT length at the time of synthesis, the more likely damage such as fracture or severance is to occur during dispersion, so it is preferable that the average length of the CNTs at the time of synthesis is 5000 μm or less. Furthermore, the aspect ratio (length / diameter) of the CNTs is preferably greater than 10. If the aspect ratio of the CNTs is greater than 10, the film state of the catalyst layer can be effectively maintained. The aspect ratio of the CNTs can be determined by measuring the diameter and length of 100 randomly selected CNTs using a transmission electron microscope and calculating the average value of the ratio of diameter to length (length / diameter).

[0038] Furthermore, the BET specific surface area of ​​CNT is 600m 2 It is preferable that it be 1 / g or more, and 800m 2 It is even more preferable that it be 2500m or more per gram. 2 It is preferable that it be less than / g, and 1200m 2 It is even more preferable that the BET specific surface area of ​​the CNT is 600 m² or less. 2 If the amount is greater than / g, electron transfer in the catalyst layer will be efficient. Also, the BET specific surface area of ​​the CNT is 2500m². 2 If the value is less than / g, it is possible to suppress the aggregation of CNTs and improve the dispersibility of CNTs in the catalyst layer. In this invention, "BET specific surface area" refers to the nitrogen adsorption specific surface area measured using the BET method.

[0039] <<Other conductive carbon materials>> Other conductive carbon materials (other conductive carbon materials) included in the catalyst layer, besides the porous carbon materials and CNTs mentioned above, include graphite-based carbon materials such as fullerenes and graphene; amorphous carbon materials such as carbon black (e.g., acetylene black, Ketjenblack®, furnace black, etc.) and fullerene soot. These can be used individually or in combination of two or more.

[0040] As other conductive carbon materials included in the catalyst layer, carbon black is preferred, and acetylene black is more preferred. As described above, a conductive layer may be provided in the support used in the present invention, but by using carbon black as the conductive carbon material, the interfacial resistance between the catalyst layer and the conductive layer can be lowered, the film state of the catalyst layer can be maintained well, and the curve factor of the photoelectric conversion element can be made even better.

[0041] Furthermore, the average primary particle diameter of the other conductive carbon material is preferably 10 nm or more, more preferably 20 nm or more, even more preferably 30 nm or more, preferably 70 nm or less, more preferably 60 nm or less, and even more preferably 50 nm or less. If the average primary particle diameter of the other conductive carbon material is above the lower limit, the moldability of the counter electrode for the photoelectric conversion element will be excellent. Also, if the average primary particle diameter of the other conductive carbon material is below the upper limit, the contact resistance of the photoelectric conversion element can be efficiently reduced. Furthermore, the average primary particle size of other conductive carbon materials can be determined by observing them with a transmission electron microscope, measuring the particle size based on images of 100 randomly selected particles of other conductive carbon materials, and then calculating the average value.

[0042] <<Other ingredients>> Other components that may be optionally included in the catalyst layer are not limited to those mentioned above, and include, for example, dispersants and thickeners. Examples of dispersants include copolymers of styrene and methoxypolyethylene glycol methacrylate, polyvinylpyrrolidone, polyoxyethylene alkyl ethers (where the alkyl group has 8 to 20 carbon atoms), and polyoxyethylene alkylphenyl ethers (where the alkyl group has 8 to 9 carbon atoms). The dispersant may be used individually or in combination of two or more.

[0043] In particular, from the viewpoint of increasing the film strength of the catalyst layer and further improving the conversion efficiency of the resulting photoelectric conversion element, nonionic polymers are preferred as dispersants, copolymers of styrene and methoxypolyethylene glycol methacrylate are more preferred, polyvinylpyrrolidone is more preferred, and copolymers of styrene and methoxypolyethylene glycol methacrylate are even more preferred.

[0044] Examples of thickening agents include cellulosic polymers (such as hydroxyethylcellulose and carboxymethylcellulose), polyethylene oxide, and polyvinyl alcohol. A single thickening agent may be used, or two or more may be used in combination. In particular, nonionic polymers (such as polyethylene oxide and hydroxyethylcellulose) are preferred as thickeners from the viewpoint of further improving the film strength of the conductive film and the conversion efficiency of the photoelectric conversion element.

[0045] The method for manufacturing the counter electrode of the present invention described above is not particularly limited. Preferably, the counter electrode of the present invention is manufactured by the method for manufacturing a counter electrode for a photoelectric conversion element of the present invention described below.

[0046] (Method for manufacturing counter electrodes for photoelectric conversion elements) The present invention provides a method for manufacturing a counter electrode for a photoelectric conversion element, which includes at least a step of forming a catalyst layer on a support using a composition comprising a porous carbon material containing two or more transition metals, CNTs, and a conductive carbon material other than the porous carbon material containing two or more transition metals and CNTs (other conductive carbon material). Herein, the present invention relates to a method for manufacturing a counter electrode for a photoelectric conversion element, characterized in that the porous carbon material containing two or more transition metals is a zeolite imidazolate framework carbide of two or more types, and the micropore capacity of the zeolite imidazolate framework carbide is 0.09 mL / g or more. Furthermore, the present invention relates to a method for manufacturing a counter electrode for a photoelectric conversion element, which includes a catalyst layer formation step and has the above characteristics, making it possible to manufacture a photoelectric conversion element with excellent current density and conversion efficiency.

[0047] Furthermore, the method for manufacturing a counter electrode for a photoelectric conversion element of the present invention optionally further includes, before the catalyst layer formation step described above, a step of obtaining a zeolite imidazolate framework carbide containing two or more transition metals from a zeolite imidazolate framework containing two or more transition metals (carbide preparation step). Furthermore, the method for manufacturing a counter electrode for a photoelectric conversion element of the present invention may further include steps other than the catalyst layer formation step and the carbide preparation step described above (other steps).

[0048] <Catalyst layer formation process> In the catalyst layer formation step, a catalyst layer is formed on a support using a composition that includes a porous carbon material containing two or more transition metals, CNTs, and other conductive carbon materials.

[0049] <<Support>> As a support, for example, those described above in the section on "Counter electrodes for photoelectric conversion elements" can be used.

[0050] <<Composition>> The porous carbon material containing two or more transition metals, CNTs, other conductive carbon materials, and other components used in the catalyst layer formation process can be those described above in the section on "Counter electrodes for photoelectric conversion elements." Therefore, the preferred types and attributes of each component used in the catalyst layer formation process are as described above in the section on "Counter electrodes for photoelectric conversion elements."

[0051] Furthermore, the composition preferably further contains a solvent. That is, the composition is preferably in the form of a dispersion in which porous carbon material, CNTs and other conductive carbon materials are dispersed in a solvent. When the composition contains a solvent, the catalyst layer consists of a dried product of the composition and usually contains porous carbon material, CNTs and other conductive carbon materials, and optionally contains other components. The components contained in the catalyst layer are those contained in the above composition, and the preferred ratio of each component is the same as the preferred ratio of each component in the composition.

[0052] The solvent used in the dispersion is not particularly limited, but it is preferably water-containing, and in addition to water, a solvent miscible with water can be used. Examples of solvents miscible with water include ethers (dioxane, tetrahydrofuran, methyl cellosolve, ethylene glycol dimethyl ether, ethylene glycol butyl ether, etc.), ether alcohols (ethoxyethanol, methoxyethoxyethanol, etc.), esters (methyl acetate, ethyl acetate, etc.), ketones (acetone, methyl isobutyl ketone, cyclohexanone, methyl ethyl ketone, etc.), alcohols (methanol, ethanol, isopropanol, propylene glycol, ethylene glycol, diacetone alcohol, phenol, etc.), lower carboxylic acids (acetic acid, etc.), amines (triethylamine, trimethanolamine, etc.), nitrogen-containing polar solvents (N,N-dimethylformamide, nitromethane, N-methylpyrrolidone, acetonitrile, etc.), and sulfur compounds (dimethyl sulfoxide, etc.). These may be used individually or in combination of two or more.

[0053] The method for preparing the dispersion is not particularly limited. For example, it can be prepared by adding the various components mentioned above to a solvent containing water and performing known mixing and dispersion treatments. Examples of known mixing and dispersion treatments include using wet jet mills such as nanomizers and ultimateizers, high-pressure homogenizers, ultrasonic dispersers, and ball mills. The temperature during the mixing and dispersion process is not particularly limited, but is preferably 60°C or lower, and more preferably 40°C or lower.

[0054] The catalyst layer can then be formed, for example, using the following method. 1) A method of applying a dispersion to the surface of a support and then drying it; 2) A method of immersing a support in a dispersion and then drying it; and 3) A method in which a dispersion is applied to a release substrate, dried to produce a catalyst layer, and the obtained catalyst layer is transferred to the surface of a support. Among these methods, method 1) is particularly preferred because it allows for easy control of the thickness of the catalyst layer.

[0055] The method for applying the dispersion to the surface of the support using the method described in 1) above is not particularly limited and any known method can be used. Specifically, the application method can be the doctor blade method, the reverse roll method, the direct roll method, the gravure method, the extrusion method, the brush application method, etc. In this case, the dispersion may be applied to only one side of the support or to both sides. The thickness of the coating film on the support before drying after application can be appropriately set according to the thickness of the catalyst layer obtained after drying.

[0056] The method for drying the dispersion on the support is not particularly limited and any known method can be used, such as drying with warm air, hot air, or low-humidity air, vacuum drying, or drying by irradiation with infrared rays or electron beams. By drying the dispersion on the support in this way, a catalyst layer can be formed on the support, and a counter electrode comprising the support and the catalyst layer can be obtained.

[0057] <Carbide preparation process> In the carbide preparation step, a zeolite imidazolate framework carbide containing two or more transition metals is obtained from a zeolite imidazolate framework containing two or more transition metals. The method for obtaining a zeolite imidazolate framework carbide containing two or more transition metals from a zeolite imidazolate framework containing two or more transition metals is not particularly limited, but a method of heating the zeolite imidazolate framework containing two or more transition metals under a reducing atmosphere is preferred.

[0058] In the carbide preparation process, the zeolite imidazolate framework containing two or more transition metals typically includes organic ligands in addition to the two or more transition metals. Examples of such organic ligands include 2-methylimidazole, terephthalic acid, benzimidazole, 2-ethylimidazole, purine, 1H-imidazo[4,5-b]pyridine, and imidazole-2-carboxyaldehyde. Among these, 2-methylimidazole is preferred. Furthermore, the zeolite imidazolate framework used as a raw material may contain only one type of organic ligand, or it may contain two or more types of organic ligands.

[0059] Furthermore, when a zeolite imidazolate framework is heated, the organic ligands in the framework are thermally decomposed, so the resulting zeolite imidazolate framework carbide usually does not contain organic ligands.

[0060] The heating temperature of the zeolite imidazolate framework in the carbide preparation step is preferably 750°C or higher, preferably 900°C or lower, more preferably 850°C or lower, and even more preferably 800°C or lower. If the heating temperature is within the above range, good dispersibility of the dispersion used to form the catalyst layer can be ensured, and the current density and conversion efficiency of photoelectric conversion elements such as dye-sensitized solar cells can be further improved.

[0061] Furthermore, a reducing atmosphere in the carbide preparation process can be achieved, for example, by supplying a mixed gas of hydrogen and an inert gas (such as nitrogen or a noble gas) into the system.

[0062] <Other processes> Other steps include, for example, a step of mixing a solution containing a transition metal-containing compound with a solution containing a compound that will become an organic ligand to obtain a zeolite imidazolate framework containing two or more transition metals (precursor preparation step), and a step of subjecting the zeolite imidazolate framework carbide to a dispersion treatment (dispersion treatment step).

[0063] The precursor preparation step can be carried out, for example, by mixing a solution containing a transition metal-containing compound with a solution containing a compound that can form an organic ligand in the zeolite imidazolate framework, thereby precipitating a metal complex in which the organic ligand coordinates to the transition metal ion. As the solution containing the transition metal-containing compound, a solution in which two or more transition metal-containing compounds are dissolved in a solvent can be used. In this case, by using two or more transition metal-containing compounds containing different transition metals in combination, two or more transition metals can be incorporated into the zeolite imidazolate framework. Specifically, for example, when preparing a zeolite imidazolate framework containing zinc and cobalt as transition metals, a zinc-containing compound such as zinc nitrate hexahydrate and a cobalt-containing compound such as cobalt nitrate hexahydrate can be used in combination as the transition metal-containing compounds. Furthermore, as a solution containing a compound that can form an organic ligand in the zeolite imidazolate framework, a solution can be used in which a compound that serves as the basis for the organic ligand (e.g., 2-methylimidazole) is dissolved in a solvent.

[0064] Furthermore, water or a solvent miscible with water is used as the solvent for solutions containing transition metal-containing compounds, and for solutions containing compounds that can form organic ligands in the zeolite imidazolate framework. Examples of solvents miscible with water include alcohols such as ethanol and propanol; ether alcohols such as ethoxyethanol and methoxyethoxyethanol; ethers such as tetrahydrofuran and methyl cellosolve; ketones such as acetone and methyl ethyl ketone; and nitrogen-containing polar solvents such as N,N-dimethylformamide and acetonitrile. Among these, a solvent miscible with water is preferred, with C1-C3 alcohols, C1-C3 ethers, and C1-C3 ketones being more preferred, C1-C3 alcohols being even more preferred, and methanol being particularly preferred. Note that a single solvent may be used, or two or more may be used in combination.

[0065] A solution containing a transition metal-containing compound may be mixed with a solution containing a compound capable of forming an organic ligand in a zeolite imidazolate framework to precipitate the desired metal complex, which is formed by the coordination of the organic ligand to the transition metal ion. The precipitated metal complex may then be isolated by filtration or decantation and washed as necessary. As the solvent used for washing, water or a solvent miscible with water as described above can be used.

[0066] Furthermore, the dispersion process can be carried out using mixers such as bead mills, ball mills, sand mills, pigment dispersers, lye crushers, ultrasonic dispersers, homogenizers, planetary mixers, and film mixers. As described above, the dispersion process can be used to adjust the BET specific surface area and pore characteristics of the zeolite imidazolate framework carbide.

[0067] (Dye-sensitized solar cells) The dye-sensitized solar cell of the present invention has a photoelectrode, an electrolyte layer, and a counter electrode in that order, and the counter electrode is the counter electrode for the photoelectric conversion element of the present invention. Since the dye-sensitized solar cell of the present invention has the counter electrode for the photoelectric conversion element of the present invention described above, it has excellent current density and conversion efficiency.

[0068] The following describes the general structure of the dye-sensitized solar cell of the present invention, but the present invention is not limited thereto.

[0069] As shown in Figure 1, the dye-sensitized solar cell 100 according to the present invention has a photoelectrode 10, an electrolyte layer 20, and a counter electrode 30.

[0070] The photoelectrode 10 comprises a support 10a, a conductive layer 10b formed on the support 10a, a porous semiconductor nanoparticle layer 10c made of semiconductor nanoparticles, and a sensitizing dye layer 10d made of sensitizing dyes adsorbed on the surface of the semiconductor nanoparticles of the porous semiconductor nanoparticle layer 10c, with the porous semiconductor nanoparticle layer 10c and the sensitizing dye layer 10d formed on the conductive layer 10b. The counter electrode 30 comprises a support 30a, a conductive layer 30b arbitrarily formed on the support 30a, and a catalyst layer 30c formed on the conductive layer 30b. Furthermore, the conductive layer 10b of the photoelectrode 10 and the conductive layer 30b of the counter electrode 30 are connected via an external circuit 40.

[0071] <Photoelectrode> The photoelectrode 10 is an electrode that can emit electrons into an external circuit when it receives light. As the support 10a for the photoelectrode, a known material can be used. Specifically, as the support 10a for the photoelectrode, the same material as described above as the "support for the counter electrode" can be used.

[0072] As the conductive layer 10b of the photoelectrode, a known conductive film can be used. Known conductive films include conductive films made of oxides such as indium tin oxide (ITO) and indium zinc oxide (IZO), conductive films made of conductive polymers such as polythiophenes and polyanilines, such as PEDOT [poly(3,4-ethylenedioxythiophene)] / PSS (polystyrene sulfonic acid), and conductive films containing conductive carbon such as natural graphite, activated carbon, artificial graphite, graphene, and CNTs.

[0073] The porous semiconductor nanoparticle layer 10c of the photoelectrode can be formed using, for example, metal oxide particles (semiconductor nanoparticles) such as titanium dioxide, zinc oxide, or tin oxide. The metal oxide particles may be used individually or in combination of two or more types. The porous semiconductor microparticle layer 10c can be formed by methods such as pressing, hydrothermal decomposition, electrophoretic deposition, and binder-free coating.

[0074] Furthermore, examples of sensitizing dyes that adsorb to the surface of the semiconductor nanoparticles in the porous semiconductor nanoparticle layer 10c to form the sensitizing dye layer 10d include organic dyes such as cyanine dyes, merocyanine dyes, oxonol dyes, xanthene dyes, squalylium dyes, polymethine dyes, coumarin dyes, riboflavin dyes, and perylene dyes; and metal complex dyes such as phthalocyanine complexes and porphyrin complexes of metals such as iron, copper, and ruthenium. The sensitizing dyes may be used individually or in combination of two or more types. The sensitizing dye layer 10d can be formed, for example, by immersing the porous semiconductor microparticle layer 10c in a sensitizing dye solution or by coating the porous semiconductor microparticle layer 10c with the sensitizing dye solution.

[0075] <Electrolyte layer> The electrolyte layer 20 typically contains a supporting electrolyte, a redox pair (a pair of chemical species that can reversibly interconvert into an oxidized and reduced form in a redox reaction), a solvent, and the like.

[0076] Examples of supporting electrolytes include salts containing cations such as lithium ions, imidazolium ions, and quaternary ammonium ions. These may be used individually or in combination of two or more. Furthermore, the redox pair can be any pair capable of reducing the oxidized sensitizing dye, such as chlorine compounds-chlorine, iodine compounds-iodine, bromine compounds-bromine, cobalt(III)-cobalt(II) ion, vanadium(III)-vanadium(II) ion, manganate ion-permanganate ion, ferricyanide-ferrocyanide, quinone-hydroquinone, fumaric acid-succinic acid, etc. These can be used individually or in combination of two or more.

[0077] Furthermore, while not particularly limited, aprotic polar substances can be used as solvents. Examples of aprotic polar substances include five-membered cyclic carbonates such as ethylene carbonate and propylene carbonate (propylene carbonate); five-membered cyclic esters such as γ-butyrolactone and γ-valerolactone; aliphatic nitriles such as acetonitrile, 3-methoxypropionitrile, and methoxyacetonitrile; aliphatic chain ethers such as dimethoxyethane and triethylene glycol monomethyl ether; aliphatic cyclic ethers such as tetrahydrofuran and dioxane; aliphatic sulfones such as ethyl isopropyl sulfone; cyclic sulfones such as sulfolane; aliphatic sulfoxides such as dimethyl sulfoxide; dimethylformamide; and ethylmethylimidazolium bistrifluoromethylsulfonylimide. These may be used individually or in combination of two or more. Among these, acetonitrile, γ-butyrolactone, 3-methoxypropionitrile, and triethylene glycol monomethyl ether are preferred.

[0078] The electrolyte layer 20 can be formed by coating a solution (electrolyte) containing its constituent components onto the photoelectrode 10, or by fabricating a cell having the photoelectrode 10 and a counter electrode 30 and injecting the electrolyte into the gap between them.

[0079] <Counter electrode> The counter electrode 30 is a counter electrode for a photoelectric conversion element of the present invention, and consists of a conductive layer 30b arbitrarily formed on a support 30a and a catalyst layer 30c formed on the conductive layer 30b. As the support 30a of the counter electrode, the same material as described above as the "support for the counter electrode" can be used. Also, as the conductive layer 30b of the counter electrode, the same material as described above as the "conductive layer for the photoelectrode" can be used.

[0080] <Manufacturing method for dye-sensitized solar cells> The method for manufacturing the dye-sensitized solar cell of the present invention is not particularly limited, but a preferred method is one that uses the counter electrode of the present invention and includes the step of forming an electrolyte layer between the photoelectrode and the counter electrode using an electrolyte solution containing an aprotic polar substance as a solvent, because it is possible to efficiently manufacture a dye-sensitized solar cell with excellent conversion efficiency.

[0081] (Solar modules) The solar cell module of the present invention is comprised of dye-sensitized solar cells of the present invention connected in series and / or in parallel. Here, a solar cell module can be obtained, for example, by arranging the dye-sensitized solar cells of the present invention in a planar or curved shape, providing non-conductive partitions between each cell, and electrically connecting the photoelectrode and counter electrode of each cell using a conductive material. Furthermore, the number of dye-sensitized solar cells used in forming the solar cell module is not particularly limited and can be appropriately determined according to the desired voltage. [Examples]

[0082] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" representing quantities refer to mass unless otherwise specified. The measurements and evaluations in this example were performed by the following methods.

[0083] <Average Particle Diameter> After subjecting the zeolite imidazolate framework carbide to platinum sputtering treatment, 100 particles of the zeolite imidazolate framework carbide were observed using a field emission scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, product name "SU-8000"), and the particle diameters thereof were measured. Then, the average particle diameter was determined as the average value of the particle diameters of the 100 zeolite imidazolate framework carbide particles. FIG. 2 shows an example of an observation image of the zeolite imidazolate framework carbide obtained by the field emission scanning electron microscope. The zeolite imidazolate framework carbide in the catalyst layer can be separated by, for example, the following method. First, water is added to carbon powder scraped out from the catalyst layer formed on a support in a sample bottle, followed by ultrasonic dispersion to obtain a black suspension. This suspension is subjected to suction filtration through a glass filter with a pore size of 2.7 μm, so as to separate into black powder (CNT) on the filter paper and a dark black filtrate (containing the zeolite imidazolate framework carbide and other conductive carbon materials). Next, the obtained filtrate is filtered through a membrane filter with a pore size of 0.45 μm, so as to separate into a black solid (the zeolite imidazolate framework carbide and other conductive carbon materials) on the filter paper and a colorless transparent filtrate. Finally, the zeolite imidazolate framework carbide and the other conductive carbon materials are separated by centrifugation utilizing the difference in specific gravity. <BET Specific Surface Area, Pore Characteristics> The BET specific surface area and pore properties (micropore capacity, mesopore capacity, and total pore capacity) of the zeolite imidazolate framework carbide were measured using the volumetric method with an adsorption measurement device (QUADRASORB SI, manufactured by Quantachrome Instruments). As a pretreatment, the sample was vacuum-heated at 200°C for 2 hours. Nitrogen adsorption measurements were performed at 77K with a relative pressure P / P0 in the range of 0 to 1. The BET specific surface area, micropore capacity, and total pore capacity were calculated using the pore analysis software QuadraWin (manufactured by Quantachrome Instruments). The BET specific surface area was calculated using the BET multipoint method, the total pore capacity using the density functional theory, and the micropore capacity using the DR method. The mesopore capacity was calculated by subtracting the micropore capacity from the total pore capacity. <Dispersibility> The dispersibility of the dispersion was evaluated 24 hours after preparation using the particle gauge method according to JIS K5600-2-5. A lower value obtained by the particle gauge method indicates higher dispersibility of the dispersion. A: The value evaluated by the grain gauge method is less than 5 μm. B: Values ​​evaluated by the grain gauge method are between 5 μm and less than 10 μm. C: Value evaluated by grain gauge method is 10 μm or more and less than 20 μm. D: Value evaluated by grain gauge method is 20 μm or larger. <Performance of dye-sensitized solar cells> As the light source, a simulated sunlight irradiation device (PEC-L11 model, manufactured by Pexel Technologies) consisting of a 150W xenon lamp light source fitted with an AM1.5G filter was used. The light intensity was 1 Sun (AM1.5G, 100mW / cm²). 2 The solar cells were adjusted to Class A (JISC8912). The fabricated dye-sensitized solar cells were connected to a source meter (Type 2400 source meter, manufactured by Keithley Corporation), and the following current-voltage characteristics were measured. Under 1 Sun light irradiation, the output current was measured while changing the bias voltage from 0V to 0.8V in 0.01V increments. The output current measurement was performed by integrating values from 0.05 seconds to 0.15 seconds after changing the voltage at each voltage step. A measurement was also performed in which the bias voltage was changed in the reverse direction from 0.8V to 0V, and the average value of the forward and reverse direction measurements was taken as the photocurrent. From the above measurement results of current-voltage characteristics, the short-circuit current density (J sc ; unit is [mA / cm 2 ), open-circuit voltage (V oc ; unit is [V]), fill factor (FF; dimensionless quantity), and energy conversion efficiency (η; unit is [%]) were calculated, and each was evaluated according to the following criteria. <<Short-circuit current density>> A: 8.6 or more B: 8.0 or more and less than 8.6 C: 7.0 or more and less than 8.0 D: less than 7.0 <<Open-circuit voltage>> A: 0.68 or more B: 0.67 or more and less than 0.68 C: 0.66 or more and less than 0.67 D: less than 0.66 <<Fill factor>> A: 0.53 or more B: 0.52 or more and less than 0.53 C: 0.51 or more and less than 0.52 D: less than 0.51 <<Energy conversion efficiency>> A: 3.10 or more B: 2.95 or more and less than 3.10 C: 2.80 or more and less than 2.95 D: less than 2.80

[0084] (Example 1) <Preparation of zeolite imidazolate framework carbide> Solution A was prepared by adding 10 L of methanol to 234 g of cobalt nitrate hexahydrate and 120 g of zinc nitrate hexahydrate to dissolve them, and Solution B was prepared by adding 10 L of methanol to 394 g of 2-methylimidazole to dissolve it. The above-mentioned solutions A and B were mixed to precipitate the precursor, and the mixture was stirred at room temperature for 20 hours. The supernatant was then removed by decantation, and the precursor was washed twice with methanol. The obtained precursor was dried at 100°C, and then calcined at 750°C for 1 hour under a hydrogen / nitrogen mixed gas atmosphere with a hydrogen concentration of 2 vol% to obtain a zeolite imidazolate framework carbide. <Preparation of dispersion> In a 500mL poly bottle, single-walled carbon nanotubes (SGCNT, manufactured by Zeon Corporation, product name "SG101"; BET specific surface area: 1264m²) are used. 2 (3.0g / g), Acetylene Black (manufactured by Denka Co., Ltd., Denka Black®, "HS-100", average primary particle size: 35nm, BET specific surface area: 68m²) 2 / g) 3.0g, a copolymer of styrene and methoxypolyethylene glycol methacrylate as a dispersant (manufactured by Kusumoto Chemical Co., Ltd., product name "Disparon (registered trademark)", glycol chain portion "(CH2-CH2-O) n A mixture was obtained by adding 6.0 g of the pure component of the sample (n=23) (200 parts per 100 parts of single-walled carbon nanotubes), 1.0 g of hydroxyethylcellulose (manufactured by Daicel Finechem, product name "SP600") as a thickener (33 parts per 100 parts of single-walled carbon nanotubes), 0.3 g of zeolite imidazolate framework carbide (10 parts per 100 parts of stoichiometric carbon nanotubes), and 400 g of pure water. The resulting mixture was stirred in a homomixer at 6000 rpm for 30 minutes while cooling the polybin to 25°C in a water bath to obtain a crude dispersion. The obtained crude dispersion was subjected to a wet jet mill (manufactured by Yoshida Machinery Industry Co., Ltd., product name "NanoVeta®") for 10 passes at 100 MPa while cooling the dispersion to 25°C to obtain a dispersion. The dispersibility of the obtained dispersion was evaluated. The results are shown in Table 1. <Fabrication of counter electrodes> The dispersion prepared as described above was coated onto a polyethylene terephthalate film (ITO-PET film, 50 mm × 50 mm, sheet resistance: 15 Ω / sq.) having a conductive film of indium tin oxide on one side by screen printing using a 100-mesh screen. The film was then dried in an inert oven (manufactured by Yamato Scientific Co., Ltd.) in an air atmosphere at 125°C for 15 minutes to obtain a counter electrode with a catalyst layer 3 μm thick formed on the support. The average particle size, BET specific surface area, and pore characteristics were evaluated using this counter electrode. The results are shown in Table 1. <Fabrication of photoelectrodes> A sensitizing dye solution (concentration 0.3 mM) was prepared using ruthenium complex N719 (manufactured by Solaronics) as the sensitizing dye and ethanol as the solvent. An isopropyl alcohol solution of titanium isopropoxide with a concentration of 5 mM was applied to an ITO-PET film (50 mm x 50 mm, sheet resistance: 15 Ω / sq.) using the bar coating method and dried in an electric furnace at 150°C for 15 minutes. A thermosetting Ag paste (manufactured by Toyo Chem Co., Ltd.) was printed using a screen printing machine (Seria SFA-PC610CTN), heated in an electric furnace at 130°C for 30 minutes, and removed to form an electrode (thickness: 8 μm). Furthermore, titanium dioxide paste (manufactured by Pexel Technologies Co., Ltd., product name "PECC-C01-06") was applied in a φ7 mm shape using a screen printing machine and dried in an electric furnace at 150°C for 15 minutes to form a porous semiconductor layer (the thickness of the titanium dioxide layer was 8 μm). The ITO-PET film with this porous semiconductor layer was placed in a sensitizing dye solution (50 cm square tray) prepared as described above, and immersed at 40°C for 2 hours. After immersion, it was washed with ethanol solution, and a photoelectrode was prepared. <Manufacturing of solar cells> An electrolyte was obtained by dissolving iodine (0.05 mol / L), lithium iodide (0.1 mol / L), t-butylpyridine (0.5 mol / L), and 1,2-dimethyl-3-propylimidazolium iodide (0.6 mol / L) in γ-butyrolactone as a solvent. Using a bonding device, the counter electrode and the photoelectrode were heat-pressed together with a Saarleen film. Then, the electrolyte was injected through an injection hole provided on the counter electrode side, and the injection hole was sealed with a photocurable resin and cured to manufacture a dye-sensitized solar cell. The short-circuit current density, open-circuit voltage, curve factor, and energy conversion efficiency were evaluated using this dye-sensitized solar cell. The results are shown in Table 1.

[0085] (Example 2) Dispersion, counter electrode, photoelectrode, and solar cell were prepared in the same manner as in Example 1, except that a zeolite imidazolate framework carbide prepared as described below was used. Evaluation was then performed in the same manner as in Example 1. The results are shown in Table 1. <Preparation of Zeolite Imidazolate Framework Carbide> Zeolite imidazolate framework carbide was prepared in the same manner as in Example 1, except that 6 g of the zeolite imidazolate framework carbide from Example 1 and approximately 160 g of 10 mm zirconia balls were added to a 100 mL container and dispersed using a ball mill for 16 hours.

[0086] (Example 3) Except for changing the heating temperature from 750°C to 850°C during the preparation of the zeolite imidazolate framework carbide, the zeolite imidazolate framework carbide, dispersion, counter electrode, photoelectrode, and solar cell were prepared in the same manner as in Example 1. The evaluation was then performed in the same manner as in Example 1. The results are shown in Table 1.

[0087] (Example 4) Except for changing the heating temperature from 750°C to 900°C during the preparation of the zeolite imidazolate framework carbide, the zeolite imidazolate framework carbide, dispersion, counter electrode, photoelectrode, and solar cell were prepared in the same manner as in Example 1. The evaluation was then performed in the same manner as in Example 1. The results are shown in Table 1.

[0088] (Comparative Example 1) Except for changing the heating temperature from 750°C to 950°C during the preparation of the zeolite imidazolate framework carbide, the zeolite imidazolate framework carbide, dispersion, counter electrode, photoelectrode, and solar cell were prepared in the same manner as in Example 1. The evaluation was then performed in the same manner as in Example 1. The results are shown in Table 1.

[0089] (Comparative Example 2) Zeolite imidazolate framework carbides and dispersions were prepared in the same manner as in Example 1, except that the heating temperature was changed from 750°C to 1000°C during the preparation of the zeolite imidazolate framework carbides. The evaluation was then carried out in the same manner as in Example 1. The results are shown in Table 1. Note that the dispersibility of the dispersion was extremely low, and it was not possible to form a catalyst layer on the support; therefore, it was not possible to evaluate the current density, open-circuit voltage, curve factor, and conversion efficiency.

[0090] (Comparative Example 3) Dispersion, counter electrode, photoelectrode, and solar cell were prepared in the same manner as in Example 1, except that a zeolite imidazolate framework carbide prepared as described below was used. Evaluation was then performed in the same manner as in Example 1. The results are shown in Table 1. <Preparation of Zeolite Imidazolate Framework Carbide> A zeolite imidazolate framework carbide was prepared in the same manner as in Example 2, except that Solution A was prepared by dissolving 53.6 g of zinc nitrate hexahydrate in 1.6 L of methanol, and Solution B was prepared by dissolving 83.6 g of 2-methylimidazole in 1.6 L of methanol.

[0091] (Comparative Example 4) Dispersion, counter electrode, photoelectrode, and solar cell were prepared in the same manner as in Example 1, except that a zeolite imidazolate framework carbide prepared as described below was used. Evaluation was then performed in the same manner as in Example 1. The results are shown in Table 1. <Preparation of Zeolite Imidazolate Framework Carbide> A zeolite imidazolate framework carbide was prepared in the same manner as in Example 2, except that Solution A was prepared by dissolving 28.8 g of cobalt nitrate hexahydrate in 2.0 L of methanol, and Solution B was prepared by dissolving 64.8 g of 2-methylimidazole in 2.0 L of methanol.

[0092] (Comparative Example 5) The dispersion, counter electrode, photoelectrode, and solar cell were prepared in the same manner as in Example 1, except that the zeolite imidazolate framework carbide was not added during the preparation of the dispersion. The evaluation was then performed in the same manner as in Example 1. The results are shown in Table 1.

[0093] In addition, in Table 1 shown below, "CNT" stands for carbon nanotube. "SWCNT" refers to single-walled carbon nanotubes. "AcB" stands for Acetylene Black.

[0094] [Table 1]

[0095] Table 1 shows that dye-sensitized solar cells with excellent current density and conversion efficiency can be obtained using the counter electrodes obtained in Examples 1 to 4. [Industrial applicability]

[0096] According to the present invention, it is possible to provide a counter electrode for a photoelectric conversion element that can improve the current density and conversion efficiency of the photoelectric conversion element, such as a dye-sensitized solar cell. Furthermore, according to the present invention, it is possible to provide a dye-sensitized solar cell with excellent current density and conversion efficiency, and a solar cell module using this dye-sensitized solar cell. Furthermore, according to the present invention, it is possible to provide a method for manufacturing a counter electrode for a photoelectric conversion element that can improve the current density and conversion efficiency of the photoelectric conversion element, such as a dye-sensitized solar cell. [Explanation of Symbols]

[0097] 10 Photoelectrodes 30 Counterelectrode 20 Electrolyte layer 10a,30a Support 10b,30b conductive layer 10c porous semiconductor microparticle layer 10d sensitized pigment layer 30c catalyst layer 40 circuits 100 Dye-sensitized solar cells

Claims

1. A counter electrode for a photoelectric conversion element having a support and a catalyst layer formed on the support, The catalyst layer comprises a porous carbon material containing two or more transition metals, carbon nanotubes, and conductive carbon material other than the porous carbon material containing the two or more transition metals and the carbon nanotubes. The porous carbon material containing the two or more transition metals is a zeolite imidazolate framework carbide. A counter electrode for a photoelectric conversion element, wherein the micropore volume of the zeolite imidazolate framework carbide is 0.09 mL / g or more.

2. The counter electrode for a photoelectric conversion element according to claim 1, wherein the average particle size of the zeolite imidazolate framework carbide is 0.1 μm or more and 2.0 μm or less.

3. The counter electrode for a photoelectric conversion element according to claim 1, wherein the two or more transition metals include at least one of zinc and cobalt.

4. The photoelectrode, electrolyte layer, and counter electrode are arranged in this order. A dye-sensitized solar cell, wherein the counter electrode is a counter electrode for a photoelectric conversion element according to any one of claims 1 to 3.

5. A solar cell module comprising dye-sensitized solar cells as described in claim 4, connected in series and / or in parallel.

6. The process includes forming a catalyst layer on a support using a composition comprising a porous carbon material containing two or more transition metals, carbon nanotubes, and a conductive carbon material other than the porous carbon material containing the two or more transition metals and the carbon nanotubes. The porous carbon material containing the two or more transition metals is a zeolite imidazolate framework carbide. A method for manufacturing a counter electrode for a photoelectric conversion element, wherein the micropore volume of the zeolite imidazolate framework carbide is 0.09 mL / g or more.

7. The method for manufacturing a counter electrode for a photoelectric conversion element according to claim 6, wherein the average particle size of the zeolite imidazolate framework carbide is 0.1 μm or more and 2.0 μm or less.

8. A method for manufacturing a counter electrode for a photoelectric conversion element according to claim 6 or 7, further comprising the step of heating a zeolite imidazolate framework containing two or more transition metals in a reducing atmosphere at a temperature of 750°C to 900°C before the step of forming the catalyst medium layer, to obtain the zeolite imidazolate framework carbide.

9. The method for manufacturing a counter electrode for a photoelectric conversion element according to claim 8, wherein the organic ligand contained in the zeolite imidazolate framework is 2-methylimidazole.

Citation Information

Patent Citations

  • Catalyst electrode, and dye-sensitized solar cell with it

    JP2006202562A